PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS PERMAINAN JUMANJI PADA MATERI AKU DAN KEBUTUHANKU MATA PELAJARAN IPAS KELAS IV DI SEKOLAH DASAR - Safitri, Adinda; Nirmayani, Heny; Adnyana, komang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low level of active participation and understanding among students in science learning, especially the material "Me and My Needs" in grade 4 of elementary school. The limitations of interactive and innovative learning media make the learning process less interesting and less meaningful for students. The purpose of this research is to develop a digital learning media based on the Jumanji game that is feasible and practical for use in science learning. This research applies the Research and Development (R&D) method with the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects included fourth grade students and teachers from three elementary schools in Cluster IX, Buleleng District. Data collection techniques were carried out through observation, expert validation, and practicality testing. The instruments used were validation sheets from media, material, and language experts, as well as teacher and student response questionnaires. The results showed that the developed digital learning media based on the Jumanji game obtained very high validity scores from media experts (0.95), material experts (0.94), and language experts (0.92). Furthermore, the results of the practicality test showed that the media was highly practical and capable of increasing active student participation. Therefore, the Jumanji game-based digital learning media is a viable, innovative alternative in science learning to increase student engagement and understanding.